Development and characterization of a new hydrogel based on galactomannan and κ-carrageenan. (10th December 2015) - Soares, Paulo A.G.; C de Seixas, José R.P.; Albuquerque, Priscilla B.S.; Santos, Gustavo R.C.; Mourão, Paulo A.S.; Barros, Wilson; Correia, Maria T.S.; Carneiro-da-Cunha, Maria G.
Highlights: The hydrogel of galactomannan/κ-carrageenan showed stable physical properties. The hydrogel matrix acquired higher organization over the experimental time. The matrix organization of the hydrogel showed a macropore architecture. This hydrogel is a promising biomaterial for tissue engineering applications. Abstract: A new hydrogel based on two natural polysaccharides was prepared in aqueous medium with 1.7% (w/v) galactomannan (from Cassia grandis seeds) and different concentrations of κ-carrageenan (0.3, 0.4 and 0.5% w/v), CaCl2 (0.0, 0.1 and 0.2 M) and pH (5.0, 5.5 and 6.0), using a full factorial design based on rheological parameters. The best formulation was obtained with 1.7% (w/v) galactomannan and 0.5% (w/v) κ-carrageenan, containing 0.2 M CaCl2 at pH 5.0. Nuclear magnetic resonance and scanning electron microscopy where used in order to characterize the hydrogel formulation. A shelf life study was carried out with this formulation along 90 days-period of storage at 4 °C, evaluating pH, color, microbial contamination and rheology. This hydrogel showed no significant changes in pH, no microbial contamination and became more translucent along the aging. Analyses by nuclear magnetic resonance and rheology showed a larger organization of the polysaccharides in the hydrogel matrix. The results demonstrated that this hydrogel was stable with possible applications in medical and cosmetic fields.